Recurrent pleural effusion in myeloma. Issue 8 (18th August 2022) - Woo, Wing Hang; Ithnin, Azlin; Raffali, Mohd Asyiq Al-Fard Mohd; Abd. Hamid, Mohamed Faisal; Abdul Wahid, S Fadilah; Wan Jamaludin, Wan Fariza
ABSTRACT: Plasma cell (PC) disorders make up a spectrum of diseases which include myeloma and amyloidosis. Pleural effusion in myeloma is rare and may result from myelomatous infiltration of the pleura or heart failure in cardiac amyloidosis. Benign causes of pleural effusion include infection, hypoalbuminemia or chronic renal impairment. Myelomatous pleural effusion (MPE) is diagnosed via pleural fluid cytomorphology and flow cytometry for malignant PCs, protein electrophoresis or pleural biopsy. A 74-year-old man with immunoglobulin A myeloma developed recurrent MPE with possible secondary cardiac amyloidosis. Despite achieving partial remission in serum paraprotein, the effusion was refractory to percutaneous drainage and pleurodesis. The treatment is aimed at eradicating myeloma and relieving respiratory symptoms. Early recognition of myeloma progression into extramedullary infiltration and secondary amyloidosis is important. While chemotherapy intensification in older patients can be challenging, multidisciplinary management is essential in alleviating symptoms and in improving the quality of life.